Unmanned aerial vehicle systems: ergodesign indicators - Rubtsov, Anatoly; Svirko, Vladimir; Otroumov, Ivan (Theory and practice of design, 2022)
Based on the analysis of the current state and directions of development of different unmanned aerial vehicle systems (UAVS) as well as long-term research of authors in the field of ergodesign of such systems, the article considers and substantiates the issue of creating the system of unified ergodesign indicators of the UAVS main components. The article is devoted to the problem of forming measures to improve the efficiency, safety and comfort of UAVS operation based on the targeted application of ergodesign principles and requirements for the design and operation of unmanned aerial vehicles, as well as developing a system of ergodesign indicators and methods of their evaluation during design, operation and creation of new models of UAVS. The publication is based on the authors’ experimentally proven need to take into account the fact that new models of UAVS should be created on the functional principle of designing оf processes but not products. After all, the subjective criterion for the quality of UAVS from the standpoint of ergodesign is the feeling of operators of functional comfort, when components of the technical structure are perceived as a complex of functional and spatial means that create comfortable and safe conditions for staff, and UAVS has effective technical means to implement this activities. Thus, the authors proposed such an approach to the creation of UAVS, where ergodesign is considered not only as a progressive methodology for creating and producing high quality science-intensive products, but primarily as research and development activities other than traditional product design. In a broad sense, the purpose of this approach is to ensure the effectiveness of the UAVS in all areas of application, which is achieved through synergies at different stages of the life cycle of the UAVS and especially such indicators as efficiency, safety and comfort. The first step in this direction is to determine and substantiate the list of ergodesign quality indicators of the main components of UAVS. Therefore, the purpose of the publication in its broadest sense is to study the role of the human factor in the creation and operation of UAVS and to develop the system of unified ergodesign indicators for their evaluation.